Post-Covid-19 pandemic course interest and learning: A Gender and Grade-based investigation - Arif Budi Prasetya; Muh Farozin; Budi Astuti; Rita Eka Izzaty (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2022)
This study aimed to determine 1) the relationship between course interest and learning motivation. 2) Differences in course interest and learning motivation in terms of gender and grade level after the Covid-19 Pandemic. The participants were 10th, 11th, and 12th-grade vocational high school students at Bandar Lampung. Data were collected using the Course Interest Scale (CIS) and Instructional Materials Motivation Survey (IMMS) developed by Keller and analyzed using product moment correlation, Mann-Whitney, and Kruskal Wallis.   While learning motivation and course interest exhibited a significant difference in terms of gender, no significant difference was noticed in terms of grade. This study found a significant relationship between course interest and learning motivation, with a value of 0.668. The results of this study can be used as a basis for developing a program in vocational high school context in Bandar Lampung.